Optimalisasi Supervisi Keperawatan di Masa Pandemi COVID-19 - Yuni Susiana Nur; Hanny Handiyani; Lilis Rayatin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify nurse managers' implementation of the nursing supervision function during the COVID-19 pandemic. The method used is a case study starting with data collection through interviews, surveys and document searches. The results showed that the head of the room had performed the supervisory directive function well (89%), but the nurses' perception of the implementation of nursing supervision carried out by the head of the room during the COVID-19 pandemic was sufficient (77%). In conclusion, nursing supervision activities during the COVID-19 pandemic were not optimal due to maintaining distance and minimizing close contact. The nursing supervision that can be carried out is the use of platforms to avoid direct contact and the possibility of nurses being exposed to COVID-19 infection. Keywords: COVID-19, Nursing Supervision, Digital Technology